Control Strategy of Parallel Converter for Braking Energy Feedback of Urban Rail Transit - ZHANG Tiejun; WANG Jianping; HUANG Keyuan (Kongzhi Yu Xinxi Jishu)
Braking energy can be fed back to the grid by the metro braking energy feedback converter using multiple power modules in parallel, but there are some problems such as circulating flow and harmonics. In this paper, a dual closed-loop control strategy based on carrier phase-shifting parallel mode was designed according to the operating conditions of multi-module parallel converters for urban rail transit energy feedback. Its outer loop is used to control the DC bus voltage and the inner loop is used to control power. The DC bus energy can be quickly feed back to the grid to improve the dynamic response speed of the converter. By adjusting the distribution time of zero-vector and improving the space vector modulation mode, the circulating flow between modules can be reduced and the capacity of converter can be improved. A pulse phase triggering method based on carrier phase shift was used to reduce the grid-connected harmonic current of the converter. Simulation results show that the proposed strategy has the advantages of fast dynamic response, low harmonic rate and small circulation, which meets the requirements of the parallel-converter for urban rail transit energy feedback.